The Adjunctive Effect of Quercetin on Postoperative Pain Management Following Cesarean Section: A Randomized Controlled Study - Mohamed Elmokadem E; Khaled Abou El Fadl D; Bassiouny AM; Mahmoud MMAE; Samy M; El Said NO (Drug Design, Development and Therapy)
Eman Mohamed Elmokadem,1,* Dina Khaled Abou El Fadl,1,* Ahmed M Bassiouny,2,3 Maisa Mohamed Abd Elkhalik Mahmoud,4 Mohammed Samy,5 Nouran Omar El Said1,* 1Department of Pharmacy Practice and Clinical Pharmacy, Faculty of Pharmacy, Future University in Egypt, Cairo, Egypt; 2Department of Radiodiagnosis, Faculty of Medicine, Ain Shams University, Cairo, Egypt; 3Department of Radiology, Quantum Radiology, Sydney, New South Wales, Australia; 4Department of Anesthesia, El Matarya Teaching Hospital, Cairo, Egypt; 5Department of Obstetrics and Gynecology, Faculty of Medicine, Ain Shams University, Cairo, Egypt*These authors contributed equally to this workCorrespondence: Nouran Omar El Said, Department of Pharmacy Practice and Clinical Pharmacy, Faculty of Pharmacy, Future University in Egypt, 90th Street, New Cairo, Cairo, 12311, Egypt, Tel +201006526452, Email nomar@fue.edu.egPurpose: Post-cesarean section pain management remains a crucial challenge in obstetric care, with implications for maternal recovery, mother-child bonding, and long-term health outcomes. Quercetin, a naturally occurring flavonoid with anti-inflammatory and antioxidant properties, has shown promising analgesic effects in preclinical studies but has limited clinical evidence for acute pain management. This study aimed to assess the efficacy of preoperative Quercetin administration on acute post-operative pain following cesarean section.Patients and Methods: In this prospective, double-blinded, randomized controlled trial, 80 patients undergoing elective cesarean section under spinal anaesthesia were randomly allocated to receive either 500 mg oral Quercetin (n=40) or matching placebo (n=40) one hour before surgery. The primary outcome was postoperative pain intensity assessed using a 10 cm Visual Analog Scale (VAS) at 2, 6, 12, and 24 hours after surgery. Secondary outcomes included time to first analgesic request, total morphine consumption, incidence of postoperative nausea and vomiting, time to physical activity initiation, functional activity, patient satisfaction, and adverse effects.Results: The Quercetin group demonstrated significantly lower VAS scores at all measured time points (p< 0.001) and delayed time to first analgesic request (3.9± 1.3 vs 2.73± 0.78 hours, p< 0.001) compared to the placebo group. Additionally, patients receiving Quercetin initiated physical activity significantly earlier (15.2± 1.9 vs 19.03± 2.66 hours, p< 0.001) and reported higher satisfaction levels on postoperative day 2 (p=0.042). However, total morphine consumption, functional activity, incidence of nausea and vomiting, and hospital length of stay were comparable between groups, with no significant differences in adverse effects.Conclusion: Preoperative administration of 500 mg Quercetin significantly reduced postoperative pain and delayed the need for rescue analgesia following cesarean section, allowing for earlier mobilization without increasing adverse effects. These findings suggest Quercetin may serve as a safe, effective adjunct in multimodal pain management protocols for cesarean delivery.Clinical Trial Registration: NCT06650891 (2024– 10-21).Keywords: quercetin, post-cesarean pain, analgesia, flavonoid, postoperative pain management